Sociopreneur Sebagai Tren Karir Baru dari Generasi Milenial - Mahsuni, Abdul Wahid; Supriyanto, Supriyanto; Kurniati, Kurniati (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The millennial generation, who grew up in the technological era, is a pioneer in the sociopreneurship phenomenon as a growing career trend. Their motivations involve concern for social and health issues, making them not only seekers of financial gain but also creators of real solutions to society's challenges. In facing competition and the impact of the pandemic, the enthusiasm and creativity of young sociopreneurs remains unwavering. Through marketing strategies via social media, they utilize technology to spread positive and educational messages to the public. This research, using a descriptive qualitative approach, discusses the character of young sociopreneurs from the millennial generation. The research method involved semi-structured interviews with three successful sociopreneurs, which were then analyzed using thematic analysis. The results illustrate that the sociopreneur character includes courage, creativity, and a focus on positive social change. These findings indicate that the millennial generation, with their technological understanding and humanitarian motivation, plays an important role in shaping an innovative and impactful social entrepreneurship landscape.